21 Feature tracking cardiac magnetic resonance to assess LV mechanics in different cardiac overload caused by aortic valve disease. (18th April 2016) - Scatteia, A; Vollema, E Mara; Leung, M; Marsan, N Ajmone; Baritussio, A; De Garate, E; Dastidar, A Ghosh; Rodrigues, J; Bax, JJ; Delgado, V; Bucciarelli-Ducci, C
Abstract : Background: In aortic valve disease, left ventricular (LV) dimensions and ejection fraction are important parameters for decision making. However, the effects of pressure overload caused by aortic stenosis or/and volume overload, due to aortic regurgitation, lead to different LV remodelling, concentric and eccentric hypertrophy, respectively, which may differently alter LV mechanics. We aimed to characterise LV mechanics, in terms of longitudinal strain/deformation using feature tracking cardiac magnetic resonance (FT-CMR) in patients with various degree of aortic stenosis and aortic regurgitation and preserved LV ejection fraction (LVEF). Methods: Seventy-one patients (14 with normal valve function, 29 with aortic stenosis and 28 with aortic regurgitation), mean age 45 ± 19 years, 70% men, who underwent clinically indicated CMR and showed preserved LVEF (>50%) were included. LV volumes, LVEF and mass were measured on steady-state free precession (SSFP) cine images. FT-CMR analysis was performed offline using tissue-tracking software (CVI42, Circle Cardiovascular Imaging Inc.) to estimate LV global longitudinal strain (GLS) from two long-axis SSFP cine images (Figure 1 ). To correct for the LV remodelling process, LV GLS was corrected for LV end-diastolic volume. Results: There were significant differences in LV volumes, mass and ejection fraction across the 3 groups of patients (Table 1 ): patients with aortic regurgitation showed significantly larger LV volumes, and lower LVEF compared to patients with normal aortic valve function and patients with aortic stenosis. There were no differences in LV GLS across the groups. However, after correcting for LV end-diastolic volume, patients with aortic regurgitation showed more impaired LV GLS as compared to the other groups. Conclusions: LV mechanics significantly differ across normal functioning and different type of aortic valve dysfunction (stenosis and regurgitation), with aortic regurgitation showing the most impaired LV GLS corrected for LV end-diastolic volume, despite preserved LVEF.